PORNOGRAFI DAN PORNOAKSI PERSPEKTIF AL-QUR’AN DAN HUKUM ISLAM - Mustatho, Mustatho; Nurhaliza, Febriana; Sarlina, Sarlina; Maulidya Hanafi, Lailatul (Islamic Family Law, STAI Sangatta Kutai Timur, 2025)
Pornography and pornography are social issues that have a negative impact on people's morals and morals. In the perspective of the Qur'an and Islamic law, these acts are categorized as prohibited behaviors because they are contrary to the values of holiness and ethics upheld in Islam. This research aims to examine the phenomenon of pornography and pornography that is increasingly prevalent in the perspective of the Qur'an and Islamic law. Pornography and pornography are seen as forms of deviant behavior that damage individual morals, social structures, and family orders. This research uses a qualitative method with a literature study approach that focuses on the study of Qur'anic verses, hadiths, fatwas of the Indonesian Ulema Council (MUI), and the thoughts of scholars. The findings of the study show that the Qur'an expressly prohibits all forms of actions that lead to adultery, display the aurah, and arouse orgasm, as reflected in surah al-Isra' verse 32 and al-Ahzab verse 59. In Islamic law, pornography and pornography are categorized as fahisyah (heinous acts) that are contrary to maqashid al-shariah, especially in preserving reason (hifz al-'aql) and heredity (hifz al-nasl). The MUI fatwa in 2001 also confirmed that all activities that lead to pornography and pornography are haram according to shari'i, so Islam views this phenomenon as a serious threat that must be prevented through moral, legal, and public education approaches.